FAKTOR RISIKO ANEMIA PADA SISWI PESERTA PROGRAM SUPLEMENTASI - Dodik Briawan; Ermita Arumsari; Pusporini Pusporini (Food and Nutrition Society of Indonesia, 2011)
The aim of study was to analized the risk factors of anemia among school girls participant of supplementation program. Design of this study wass cross-sectional covering 400 secondary and high school students (SMP and SMK) in Bekasi. The secondary data were analized from the baseline program of the Health Office of Bekasi. The prevalence of anemia among school girls was 38.3 percents. The significant risk factors of anemia among school girls were the age and nutritional status (IMT). The anemia risk was higher among school girls at age 13-15 years (OR = 2.73) and the thin girls (OR = 8.32).